2021
DOI: 10.2478/dim-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of User Social Support Network in Online Tumor Community

Abstract: With the development of Internet technology, online health forums have become indispensable for people who seek non-professional health support. This research focuses on the content posted by cancer patients and their relatives in online health forums and social networks to raise the following research questions: What is the overall view of the social support network in the online tumor community? What are the information behaviors of the online tumor community in different identities of users? How users inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…We have found a big gap between receiving and offering support in the DSN, which confirms Hanneman and Riddle (2005) that SNS (e.g., Facebook, Twitter) tend to show more homogeneity regarding out-degree than in-degree. In the same vein, some studies have suggested that users would restrict online support to a limited number of users (Lin and Li, 2021;Lu et al, 2021;Ramamoorthy et al, 2021). The mechanism of low out-degree and its effects on SNS should be investigated in future research.…”
Section: A B Figurementioning
confidence: 99%
See 4 more Smart Citations
“…We have found a big gap between receiving and offering support in the DSN, which confirms Hanneman and Riddle (2005) that SNS (e.g., Facebook, Twitter) tend to show more homogeneity regarding out-degree than in-degree. In the same vein, some studies have suggested that users would restrict online support to a limited number of users (Lin and Li, 2021;Lu et al, 2021;Ramamoorthy et al, 2021). The mechanism of low out-degree and its effects on SNS should be investigated in future research.…”
Section: A B Figurementioning
confidence: 99%
“…Users form supportive, asynchronous, and fulfilling relationships that reduce anxiety and improve life satisfaction in various conditions, such as cancer ( Kim et al, 2013 ; Myrick et al, 2015 ), depression ( Pan et al, 2020 ; Lu et al, 2021 ), postpartum depression ( Lei et al, 2022 ), and HIV ( Ho et al, 2017 ; Wang et al, 2018 ). On the other hand, some have indicated that passive consumption of online support can result in ineffective coping, unwanted help, negative responses, and contradicted suggestions ( Batenburg and Das, 2015 ; Hou et al, 2020 ; Lin and Li, 2021 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations